Seasonality in suicide: a study of farming suicides in England and Wales. - Simkin, S; Hawton, K; Yip, P; Yam, C (2003)
Seasonality in suicide rates has long been reported. Spring peaks in suicide deaths have been positively correlated with the proportion of the workforce engaged in agriculture. Some studies have indicated that suicides using violent methods are more likely to show seasonality. Recent research has suggested that seasonal patterns have diminished. This study examined deaths in male farmers, an occupational group which might be expected to be more vulnerable to seasonal influences because of the nature of their work and the relatively high proportion of farmers using violent methods for suicide. Data on suicides between 1982 and 1999 by males in England and Wales aged 15 years and over were provided by the Office for National Statistics. Seasonal patterns of suicide in farmers and nonfarmers were examined by nonparametric tests and harmonic analysis. No significant seasonal variation was found for farmers. For nonfarmers, although a chi-square test showed significant variation in monthly distribution, this was not found when a harmonic analysis was applied. There was no significant difference in the variation of violent suicides throughout the year. This study reinforces recent findings that seasonal variation in suicide appears to be diminishing, even in an occupational group where this might be expected.